2019
DOI: 10.1155/2019/1649279
|View full text |Cite
|
Sign up to set email alerts
|

Oral LPS Dosing Induces Local Immunological Changes in the Pancreatic Lymph Nodes in Mice

Abstract: Lacking the initial contact between the immune system and microbial-associated molecular patterns (MAMPs), such as lipopolysaccharides (LPS), early in life, may be regarded as one of the causal factors of the increasing global increase in the incidence of autoimmune diseases, such as type 1 diabetes (T1D). Previously, a reduced incidence of T1D accompanied by dramatically increased abundances of both the mucin-metabolising bacterium Akkermansia muciniphila, and LPS-carrying Proteobacteria was observed, when va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…LPSs can be involved in diabetes development, because they lead to the impairment of pancreatic β-cell function and increase the level of pro-inflammatory cytokines [ 97 ]. In mouse models, an oral injection of E. coli LPS improved local immunity, while an intraperitoneal injection of E. coli LPS improved the autoimmune response and decreased the incidence of T1D [ 98 , 99 ]. However, it is difficult to conclude whether microbial alteration is causal or consequential for T1D development.…”
Section: The Potential Role Of the Gut Microbiota In The Development Of T1dmentioning
confidence: 99%
“…LPSs can be involved in diabetes development, because they lead to the impairment of pancreatic β-cell function and increase the level of pro-inflammatory cytokines [ 97 ]. In mouse models, an oral injection of E. coli LPS improved local immunity, while an intraperitoneal injection of E. coli LPS improved the autoimmune response and decreased the incidence of T1D [ 98 , 99 ]. However, it is difficult to conclude whether microbial alteration is causal or consequential for T1D development.…”
Section: The Potential Role Of the Gut Microbiota In The Development Of T1dmentioning
confidence: 99%
“…LPS also participates in the regulation of autoimmunity, most of which are Escherichia coli LPS involved in suppressing innate immune signals, but Bacteroides dorei LPS does not show significant improvement in T1D incidence[ 94 ]. In a recent study, intraperitoneal injection of Escherichia coli LPS in T1D mice showed a decrease in the incidence of T1D and an improved autoimmune response[ 94 ], while another study of NOD mice that received oral injection of Escherichia coli LPS also demonstrated an improvement in local immunity[ 95 ]. The concept that the pathogenesis of T1D is affected by gut microbiota has been well established in mouse models, but human studies on the microbiome in T1D are still few and far between to provide convincing evidence.…”
Section: Gut Microbiota and T1dmentioning
confidence: 99%
“…It is known that Akkermansia muciniphila, belonging to the genera Akkermansia, is a mucindegrader bacterium and it has been reported to have both regulatory and inflammatory properties (64). The increase of this genus has been reported in other autoimmune pathologies, such as multiple sclerosis (64,65) and type 1 diabetes patients (66). The reasons of this increase can be found in its dual functions: it can increase to compensate for the imbalance in gut microbiota composition or it can contribute itself to the disequilibrium.…”
Section: Discussionmentioning
confidence: 99%